Novel Biomarkers and the Future Potential of Biomarkers in Inflammatory Bowel Disease - Gilles Duvoisin; Robert N. Lopez; Andrew S. Day; Daniel A. Lemberg; Richard B. Gearry; Steven T. Leach (Hindawi Limited, 2017)
There is increasing importance placed upon noninvasive assessment of gut inflammation. These tools are likely to be the key in differentiating intestinal inflammatory disease from functional disorders and in monitoring the response to intervention in individuals with known inflammatory conditions. Although various noninvasive markers are currently available, they have limitations and do not provide ideal utility. This review focuses on emerging markers of gut inflammation, highlighting the potential of specific markers.